The role of executive function in detached and positive reappraisal success - Chiew, Allison Kay-En (Nanyang Technological University, 2024)
Research has investigated the role of executive function in affecting the success of positive and detached reappraisal in downregulating negative affect, yet experimental research have found few associations between executive function (EF) components of shifting, updating, and inhibition, and the reappraisal tactics. As these studies have been conducted laboratory settings and with the same study paradigms, the generalisability and validity of the research can be called into question. This study thus aimed to examine each tactic’s reliance on EF, and the differences in this reliance, using an experience sampling procedure and through moment-to-moment measures of executive function, in a sample of young adults (N=206). Results revealed that only shifting abilities were associated with the reduction of negative affect in positive reappraisal; no other relationships were significant. The findings have particular implications for understanding the relationship between shifting abilities and the reappraisal tactics as they differ from laboratory and real-world settings.